PENGARUH METODE HYPNOTEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS IV SEKOLAH DASAR - Diana Setiana; Juvita Lathivah (Jurnal PGSD, 2020)
Topics are backgrounded by several things, among others: 1) Implementation of IPS learning process using hypnoteaching learning method, 2) student learning activities are still classified as passive, 3) Student learning outcomes have not reached the teaching completeness criteria (KKM) on the subject matter of social problems in the local environment. the problem in the research is the influence of hypnoteaching method to improve the learning result of IPS in the fourth grade students of elementary school especially the subject of social problems in the local area is still relatively low because the teacher only apply the lecture method is not included with the concrete media so that the students only accept the lessons delivered by the teacher.The method used is quantitative research, with experimental quasy design and with the research procedure consist of four phases namely (1) carry out observation, (2) learning process (3) do reflection. The instrument used is the observation sheet, the test instrument. After conducting the research, it can be seen that there is an increase of IPS lecture result in fourth grade students of Elementary School, increasing student's score seen from pretest and postes result of class student which is tested by using hypnoteaching method, 85% of students in experimental class are able to reach the above KKM. Keyword: influence of learning result of hynoteaching method